Myasthenia gravis: The evolving therapeutic landscape - Gil I. Wolfe; Jonathan E. Hanson; Nicholas J. Silvestri (eNeurologicalSci)
Pharmacological options in the management of generalized myasthenia gravis (gMG) have expanded rapidly in the last 7 years. There are now several complement inhibitors and neonatal Fc receptor antagonists on the market in many countries for patient management, following the successful completion of Phase 3 studies. In open-label extensions, these agents have proven to be effective over the longer term extending several years, with benefits such as reduction of corticosteroid requirements being observed. In the communication below, we will briefly summarize recent pharmacologic advancements in the management of gMG and outline how these agents are currently being used and may be used in the future.